Clever Maids : the Secret History of the Grimm Fairy Tales. - Paradiz, Valerie (Basic Books, 2009)
Most people know the stories of Snow White and Sleeping Beauty, but very few know that behind the Brothers Grimm and their fairy tales stood a network of sisters-and mothers, neighbors, and female friends. In this intimate history, Valerie Paradiz tells the real story of the greatest literary collaboration of the nineteenth century, and gives the long-lost narrators of these beloved tales their due. Jacob and Wilhelm Grimm were major German intellects of their time, contemporaries of both Goethe and Schiller. But as Paradiz reveals here, the romantic image of the two brothers traveling the cou.